2016
DOI: 10.1016/j.otsr.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Joint awareness after total knee arthroplasty is affected by pain and quadriceps strength

Abstract: Prospective cohort study, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
1
20
0
2
Order By: Relevance
“…Previous research evaluating recovery trajectories after TKR has established that most improvement in pain and function occurs in the first 3 months post-operative, then further small improvement up to 1 year post-operative, after which outcomes plateau [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research evaluating recovery trajectories after TKR has established that most improvement in pain and function occurs in the first 3 months post-operative, then further small improvement up to 1 year post-operative, after which outcomes plateau [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The most important finding from the present study is that FJS had a significantly lower ceiling effect and a higher floor effect within the first year after TKA. To the best of our knowledge, only two studies have investigated the use of FJS in the first year after TKA [4,11]. In one of the studies, Hamilton et al successfully validated FJS with OKS and noticed a lower ceiling effect [4], defined as scoring maximum 10% in FJS (12.6% vs. 25.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this was likely that the outcome of surgery had not reached plateau for assessment until 1 year after surgery. Nevertheless, Hiyama et al [11] reported FJS improvement within 6 months after surgery reaching a plateau from 6 to 12 months. Also, with the increasing popularity of fast-track surgery, the need for early outcome assessment has become much greater.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that when using the FJS scoring system to evaluate the difference in knee awareness of patients who underwent patellofemoral arthroplasty, unicompartmental knee arthroplasty, and TKA, they found that patients who underwent different joint arthroplasties had large differences in the FJS [13]. Hiyama et al found that quadriceps strength and pain were the main factors affecting joint awareness after TKA [26]. Quadriceps weakness is the main obstacle to patients' functional recovery after TKA, and pain is usually one of the main criteria for success or failure after TKA.…”
Section: Discussionmentioning
confidence: 99%